Analysis of UI Convenience Influence of Marketplace MobileApplication towards Consumers’ Online Buying Interset - Layla Nurul Af’idati; Richard Richard; Indry A Pradipta; Endang Retnoningsih (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2022)
The purpose of this study was to conduct an analysis to determine whether there was an effect or not of the interface convenience (user interface) of the marketplace mobile application on consumers’ online buying interest. The design method applied was the Technology Acceptance Model (TAM) which referred to the individual acceptance behavior of information technology systems. The analysis was carried out using the Structural Equation Modeling method with the Partial Least Square (SEM-PLS) model. The results achieved from this study prove that the interface convenience of the marketplace mobile application had a significant and positive effect on online buying interest in both male and female consumers. Based on the results of this study, it can be concluded that the convenience felt by consumers both male and female consumers when viewing the user interface of marketplace mobile applications will have an impact on online buying interest.